2013
DOI: 10.3382/ps.2012-02728
|View full text |Cite
|
Sign up to set email alerts
|

Influence of eggshell ultrastructural organization on hatchability

Abstract: Eggshell quality is associated with hatchability, and ultrastructural organization is an important eggshell quality parameter. To the determine the relationship of shell ultrastructural properties with hatchability, we measured the effect of eggshell thickness, mammillary layer thickness, and the average size of mammillary cones on hatchability. Eggs with thick shells and thick mammillary layers had the highest incidence of hatching. As such, hatchability correlated positively with both eggshell thickness (r =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…The distribution of mammillae and organic constituents of the scaffold affect structural aspects, such as mammillary cone size, palisade morphology, as well as mechanics of the bioceramic [46,47]. To gain a better insight, morphological features of the shell layers are revisited by applying tools of microscopy.…”
Section: Architecture Of the Organic-inorganic Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of mammillae and organic constituents of the scaffold affect structural aspects, such as mammillary cone size, palisade morphology, as well as mechanics of the bioceramic [46,47]. To gain a better insight, morphological features of the shell layers are revisited by applying tools of microscopy.…”
Section: Architecture Of the Organic-inorganic Interfacementioning
confidence: 99%
“…This suggests an interlocking of the scaffold with the palisade cones at mammillae sites, serving as a robust interface between the organic and inorganic layers of the mature biomineral. mammillary cone size, palisade morphology, as well as mechanics of the bioceramic [46,47]. To gain a better insight, morphological features of the shell layers are revisited by applying tools of microscopy.…”
Section: Architecture Of the Organic-inorganic Interfacementioning
confidence: 99%
“…The shell membranes were then carefully peeled from the edge of the sample inward (this step was missed out for cross section analysis). The egg shell samples were then boiled in 2% NaOH for 10 min to dissolve any proteinaceous material incorporated in the shell (Liao et al, 2013). After drying thoroughly at room temperature, the shell samples were then mounted on aluminium stubs using conductive silver paint (1005 aqueous conductive silver liquid-SEM adhesive, ProSciTech, Kirwan, Australia), sputter coated with gold in a Jeol MP-19020NCTR Neocoater and viewed with a XL-30 environmental scanning electron microscope (Philips, Amsterdam, The Netherlands).…”
Section: Microstructural Analysis Of Egg Shellmentioning
confidence: 99%
“…Previous studies have shown that eggshell ultrastructure organization, including eggshell thickness and mammillary layer thickness, influences both eggshell quality and egg hatchability. In addition, mammillary cone size contributes to the mechanical properties of the eggshell (Liao et al, 2013). Thus, appropriate eggshell ultrastructure organization is critical for eggshell quality in hens.…”
Section: Introductionmentioning
confidence: 99%